Almost Every Answer for Practically Any Teacher! A Resource Guide for all who desire to teach ... for lifechange! - Wilkinson, Bruce (Portland, Or. Multnoman Press, 1992)
Teachers face the threat of burnout, the challenge of discipline, and the complexity of different learning styles. Here's your chance to get a firm grasp on every issue from A to Z! This book contains 100 articles that provide insight, inspiration, and
Keywords: Christian Education; Christian education -- Teaching methods. Teaching -- Religious aspects -- Christianity. Classroom management